Effect of Nitrogen and Boron on the Growth and Yield of Tomato (Lycopersicon esculentum M.) - Haque, M. E.; Paul, A. K.; Sarker, J. R. (International Journal of Bio-resource and Stress Management, 2011)
A field experiment was conducted at the research farm of Sher-e-Bangla Agricultural University, Dhaka, during November 2006 to March 2007 to study the effects of nitrogen and boron on growth and yield of tomato. Four levels of each of Nitrogen (N0=0, N1=60, N2=120 and N3=180 kg N ha-1) and 3 levels of Boron (B0=0, B1 = 0.4 and B2= 0.6 kg B ha-1) in all possible combinations were applied following a randomized block design with three replications. The individual and combined effects of nitrogen (N) and boron (B) on growth, yield and nutrient content in plants of tomato were studied. With increasing the levels of N, all the yield contributing characters and yield of tomato increased up to the 120 kg N ha-1. Application of N @ 120 kg ha-1 gave the highest plant height (122.46 cm), flower clusters plant-1 (9.67), flowers cluster-1 (10.44), fruits cluster-1 (6.76), fruits plant-1 (52.44), fruit weight plant-1 (1.60 kg), fruit weight plot-1 (19.14 kg) and fruit yield (48.33 t ha-1). On the contrary application of B @ 0.6 kg ha-1 gave the highest values of all these parameters. In interaction, N @ 120 kg ha-1 along with B @ 0.6 kg ha-1 produced the highest plant height (142.2 cm), flower clusters plant-1 (12.67), flowers cluster-1 (11.67), fruits cluster-1 (6.33), fruits plant-1 (67.33), fruit weight plant-1 (1.953 kg), fruit weight plot-1 (23.20 kg) and fruit yield (58.59 t ha-1). The highest N and B content in plants were observed from 180 kg N ha-1. However, application of N had no significant effect on B content in plant.